Analysis of Concept Understanding Using Online Learning Based on WhatsApp Group - Rahmani, Yoga Rizqi; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Understanding the concept is a very important aspect of learning science. However, elementary students' understanding of science concepts is still low. This study aims to analyze the problems of understanding the science concept of fifth-grade elementary school students regarding human motion systems using online learning based on WhatsApp groups through video media and teaching materials. This study used the descriptive qualitative method. The research subjects were 25 students of grade V SD for the 2020/2021 academic year. The research instrument used is a matter of understanding the concept of human organ systems. The results showed that the achievement of students' concept understanding with high categories amounted to 48%, 44% medium category, and 8% low category. The overall average score points to 77.09. Thus, it can be concluded that the results of the analysis of the understanding of the science concept of fifth-grade elementary school students regarding the motion system achieved good results using online learning based on WhatsApp groups through video media and teaching materials.